Carp polyculture in aquaculture sewage treatment plant andits impact on soil and water characteristics - Bibhudatta, Mishra; Ayyappan, S; Jena, J K; Patri, Priyambada; Behera, P K; Aravindakshan, P K; Purushothaman, C S (Indian Journal of Fisheries, 2016)
The hydrobiological conditions of carp polyculture ponds in an aquaculture sewage treatment plant (ASTP) at Matgajpur,Cuttack, Orissa, with reference to sewage input and production were studied. The water quality of fish culture pond, receivingpartially treated effluent from a duckweed pond complex was evaluated for different physico-chemical and biotic parameters.Water quality parameters such as pH, total alkalinity, hardness and dissolved oxygen were found to be conducive for fishculture. Wide variations in nutrients, ammonium-N, nitrate-N, nitrite-N and phosphate-P in water and organic carbon, totalnitrogen and available phosphorus in soil showed increasing trend with time. The C/N ratio (4.2-16.7) in soil, organic matter(5.4-9.8 ppm) and plankton (652-33, 280 nos. l-1) in culture water suggest productive status of the pond. Carp polyculturewas carried out in two ponds using five species combination of rohu, catla, mrigal, silver carp and common carp resulting inproduction of 3451 kg ha-1 and 3975 kg ha-1 annually. Silver carp registered maximum growth and survival rate where ascatla showed poor performance. The water released from the carp culture pond meets the water quality criteria specified forirrigation water and swimming water. This type of carp culture in ASTP showed progressive trend in terms of safe biomassproduction (fish) and are comparable to the results obtained in other wastewater culture studies.